The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1046/j.1524-4725.2001.01043.x
|View full text |Cite
|
Sign up to set email alerts
|

Auto-Mohs.com

Abstract: Background. Over the course of the last three decades Americans have grown more and more fond of “alternative” or homeopathic medical therapies. The explosion of the Internet has made these nontraditional remedies more accessible to the general public. Objective. To describe two cases of auto‐Mohs through patient self‐application of products containing zinc chloride paste. The case of a basal cell carcinoma and the case of a squamous cell carcinoma are described. Methods. Each of our patients applied a homeopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…If the researchers analyzed websites selling prescription and over-the-counter drugs, we considered websites selling prescription drugs if it was possible to identify them. We decided to deal only with prescription drugs, although over-the-counter substances can also have negative effects on people’s health, despite the no-harm claims made by their producers, as several clinical cases demonstrate [48,49]. Although examining nonprescription drugs was not an objective of this review, it should be borne in mind that some case reports showed the presence of prescription drugs even in products that did not claim to contain them [50,51].…”
Section: Methodsmentioning
confidence: 99%
“…If the researchers analyzed websites selling prescription and over-the-counter drugs, we considered websites selling prescription drugs if it was possible to identify them. We decided to deal only with prescription drugs, although over-the-counter substances can also have negative effects on people’s health, despite the no-harm claims made by their producers, as several clinical cases demonstrate [48,49]. Although examining nonprescription drugs was not an objective of this review, it should be borne in mind that some case reports showed the presence of prescription drugs even in products that did not claim to contain them [50,51].…”
Section: Methodsmentioning
confidence: 99%
“…Direct pressure with this impregnated gauze is applied to pinpoint bleeding until hemostasis is achieved 2 . Zinc paste compounds are used in homeopathic medicine, touted as being a “natural alternative” for curing skin cancer 24 …”
Section: Caustic Agentsmentioning
confidence: 99%
“…A remarkable finding was reported for the topical application of a “homeopathic” zinc chloride paste in two patients with histologically proven epithelial skin cancer (18), which led to the disappearance of the lesions. The preparation was advertised on the Internet as a “natural” treatment modality.…”
Section: Dermatologic Applicationsmentioning
confidence: 99%